Bye-bye, bye advantage: estimating the competitive impact of rest differential in the National Football League - Lopez, Michael J.; Bliss, Thompson (Frontiers in Behavioral Economics, 2024)
The National Football League (NFL) sets its regular season schedule to optimize viewership and minimize competitive inequities. One inequity assumed to impact team performance is rest differential, defined as the relative number of days between games. Using Bayesian state space models on both game outcomes and betting market data, we estimate the competitive effect of rest differential in American football. We find that the most commonly referred to inequities—both the bye week rest advantage and the mini-bye week rest advantage— currently show no significant evidence of providing the rested team a competitive edge. Further, we trace a decline in the advantage of a bye week to a 2011 change to the NFL's Collective Bargaining Agreement, which represents a natural experiment to test the relevance of rest and preparation in football. Prior to the agreement, NFL teams off a bye week received a significant advantage (+2.2 points per game), but since 2011, that benefit has been mitigated. Our findings imply that extra days with practice time, and not extra days off alone, are the primary driver of any NFL rest advantage.